Metabolite Profiling and Transcriptome Analysis Unveil the Mechanisms of Red-Heart Chinese Fir [Cunninghamia lanceolata (Lamb.) Hook] Heartwood Coloration - Cao, Sen; Deng, Houyin; Zhao, Ye; Zhang, Zijie; Tian, Yanting; Sun, Yuhan; Li, Yun; Zheng, Huiquan (Frontiers in Plant Science, 2022)
Red-heart Chinese fir (Cunninghamia lanceolata) has the advantages of high density and attractive color, which is popular in the market as ornamental plants. Most studies about stems of woody plants have been reported only at the cytological level to date because of few living cells. In this study, the xylem was successfully partitioned into three effective sampling areas: sapwood, transition zone, and heartwood. Secondary metabolites, cell survival, and differentially expressed genes in the three sampling areas were investigated respectively. Firstly, we identified the phenylpropanoid and flavonoid pathways closely related to color. Based on the chemical structure of secondary metabolites in pathways, two notable directions had been found. Luteolin’s glycosylation products might be the key substances that regulated the color of heartwood in red-heart Chinese fir because of the 1000-fold difference between red-heart and white-heart. We also found pinocembrin and pinobanksin in Chinese fir, which were rarely reported before. At the cytological level, we believed that the transition zone of red-heart Chinese fir was a critical region for color production because of the fewer living ray parenchyma cells. In addition, transcriptome and qRT-PCR proved that genes regulating the entire phenylpropanoid pathway, upstream of the flavonoid pathway and some glycosyltransferases were significantly up-regulated in the transition zone of red-heart, and then colored the heartwood by increasing metabolites. This is the first report on the color related secondary metabolites regulated by differential genes in red-heart Chinese fir. This study will broaden our knowledge on the effects of metabolites on coloring woody plant xylems.